(3TPhQ GdPgHs - (3GHf GQaY QGSg GdCfOdSj GdLjGfj, GHf GQaY QGSg GdCfOdSj GdLjGfj,J (B593 (3g` s
(3ChdgG (B:s
(3EPG KdK GdeQjN HGdRgQI CeQA hbGQf HGdHOQ GdefjQ PcGA s
(3BNQgG (B:s
(3hEdG adG JQJY HgG agi QhVI bO GeJdCJ ddQGFOjf GdCaGYjG s
(3GdfSNI HgG MhGTs
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26s
Keywords: (3GdcjejGA h GdWHjYjGJs